Transcervical Access for Ultrasound-Guided Biopsy—A Safe Technique to Sample Apical Lung Lesions - Bellam Premnath, Krishna Prasad; Bansode, Shubhada Yadavrao (Journal of Clinical Interventional Radiology ISVIR, 2022)
Eight patients with apical lobe lung lesions referred for image-guided biopsy where the lesion was abutting the mediastinal or apical pleura, and was visible in ultrasound using a suprasternal–supraclavicular route were consented and subjected to successful ultrasound-guided transcervical biopsy using different routes based on lesion characteristics and location of vital vascular structures—either through the thyroid gland, by the side of the gland lateral to the common carotid artery, or between the thyroid gland and common carotid artery after hydrodissection. Transthyroid access was used in 50% of cases. There were no immediate or long-term complications in any patient over a mean follow-up period of 28.5 months. Sample adequacy was 100%.
Keywords: transcervical; transthyroid; lung apex; core biopsy